2020
DOI: 10.1017/s0031182020000153
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant therapies for chagasic myocarditis: a systematic review

Abstract: The aim of this review was to identify anti-inflammatory and antioxidant therapeutic agents and their effects on patients with chagasic myocarditis. A systematic review of the MEDLINE, EMBASE, WEB OF SCIENCE, SCOPUS, LILACS and CENTRAL databases (Cochrane Library) was carried out without language restrictions. The descriptors used were: ‘Chagas cardiomyopathy’, ‘treatment’, ‘Chagas disease’, ‘anti-inflammatory agents’, ‘Trypanosoma cruzi’ and ‘antioxidants’. A total of 4,138 articles was identified, six of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This is interesting as myeloid-type innate immune cells provide an immune response of metabolic reprogramming and are targets of parasitic infections such as Trypanosoma cruzi, which can compromise the liver, spleen, and lymph nodes, and cause chronic brain and cardiac inflammation that can be fatal to the individual [9]. Treatment with this drug is reflected in the improvement of cardiac function [12]. In vitro mouse models have shown that if there is an activator of SIRT1, it can suppress the oxidative stress and inflammation characteristic of the chronic phase of Chagas disease.…”
Section: Resveratrol and Sirtuinmentioning
confidence: 99%
“…This is interesting as myeloid-type innate immune cells provide an immune response of metabolic reprogramming and are targets of parasitic infections such as Trypanosoma cruzi, which can compromise the liver, spleen, and lymph nodes, and cause chronic brain and cardiac inflammation that can be fatal to the individual [9]. Treatment with this drug is reflected in the improvement of cardiac function [12]. In vitro mouse models have shown that if there is an activator of SIRT1, it can suppress the oxidative stress and inflammation characteristic of the chronic phase of Chagas disease.…”
Section: Resveratrol and Sirtuinmentioning
confidence: 99%
“…Ameliorating cardiac inflammation and oxidative damage through treatment with a SIRT1 agonist improved cardiac function, without altering cardiac parasite burden or cardiac fibrosis [174]. Antioxidant treatments are also being tested in patients, with some promise in late-stage disease, though most studies did not assess functional improvement (see [175] for a systematic review).…”
Section: Immune Modulation Through Metabolism To Improve Chagas Disea...mentioning
confidence: 99%